2011
DOI: 10.17969/agripet.v11i1.390
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Limbah Berserat Dalam Konsentrat Untuk Sapi Jantan Umur Satu Tahun

Abstract: A series of experiment had been conducted to improved the quality of rice straw, rice bran and cassava solid waste through biological pretreatment using several species of microbes. Based on the digestibility and the fermentation product, indicated that 30 percent of rice straw, 35 percent of rice bran and 35 percent of cassava solid waste was the optimal ratio for concentrate formulated. The present experiment was carried out by experimental method with Completely Randomized Design, on twelve yearling male ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
2
1
Order By: Relevance
“…The results achieved in the current study is higher than the results of Hindratiningrum et al (2011) which is 6.67-7.82 mM. Such discrepancy may occur due to the production of N-NH3 which is highly affected by several factors, including feed, mainly depending on the composition and properties of feed protein (Suwandyastuti and Rimbawanto, 2011).…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…The results achieved in the current study is higher than the results of Hindratiningrum et al (2011) which is 6.67-7.82 mM. Such discrepancy may occur due to the production of N-NH3 which is highly affected by several factors, including feed, mainly depending on the composition and properties of feed protein (Suwandyastuti and Rimbawanto, 2011).…”
Section: Resultscontrasting
confidence: 82%
“…Mean VFA results of the current study were higher than 70-130 mM of normal concentration of VFA in cattle rumen (Khampa and Wanapat, 2006). Such discrepancy may occur because the VFA production depends on the chemical composition and structure of the feed materials as well as the ratioof forage and concentrate ration (Suwandyastuti and Rimbawanto, 2011). The high concentration of VFA can be used as a measure of the energy availability in the form of ATP (Suryapratama, 1999), despite the high concentration of VFA can also be due to the lack of VFA absorption of in vitro experiments.…”
Section: Resultscontrasting
confidence: 69%
“…However, agricultural and agro-industrial by product feed conteined high percentage of fiber and difficult to be digested by animals (Suwandyastuti and Rimbawanto, 2011). Researchs conducted by scientiests indicated that pre-treatment of high fiber feed were able to improve nutrient content and digestibility of feed (Bisaria et al, 1997;Tang et al, 2008;Wanapat et al, 2009 ;Rahman et al, 2011 ;Shrivastava et al, 2011 ;Wajizah et al, 2015 ;Samadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of strategies to solve the problem was to ulilize agricultural and agro-industrial by products as animal feed. However, agricultural and agro-industrial by product feed conteined high percentage of fiber and difficult to be digested by animals (Suwandyastuti and Rimbawanto, 2011). Researchs conducted by scientiests indicated that pre-treatment of high fiber feed were able to improve nutrient content and digestibility of feed (Bisaria et al, 1997;Tang et al, 2008;Wanapat et al, 2009 ;Rahman et al, 2011 ;Shrivastava et al, 2011 ;Wajizah et al, 2015 ;Samadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%